2004
DOI: 10.1111/j.1356-9597.2004.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cryptochrome DASH from vertebrates

Abstract: A new type of cryptochrome, CRY-DASH, has been recently identified. The CRY-DASH proteins constitute the fifth subfamily of the photolyase/cryptochrome family. CRY-DASHs have been identified from Synechocystis sp. PCC 6803, Vibrio cholerae , and Arabidopsis thaliana . The Synechocystis CRY-DASH was the first cryptochrome identified from bacteria, and its biochemical features and tertiary structure have been extensively investigated. To determine how broadly the subfamily is distributed within living organisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 54 publications
6
127
0
11
Order By: Relevance
“…Wavelengths greater than 370 nm can effectively stimulate photorepair, yet the specific action spectra for these proteins in zebrafish are unknown. The closest known long wave absorbers in zebrafish are cyptochromes, which show only weak photolyase activity [26] and are thought to play larger roles in circadian rhythm [27].…”
Section: Ultraviolet Radiation Exposurementioning
confidence: 99%
“…Wavelengths greater than 370 nm can effectively stimulate photorepair, yet the specific action spectra for these proteins in zebrafish are unknown. The closest known long wave absorbers in zebrafish are cyptochromes, which show only weak photolyase activity [26] and are thought to play larger roles in circadian rhythm [27].…”
Section: Ultraviolet Radiation Exposurementioning
confidence: 99%
“…53) Seven zebrafish Cry genes (zCry1a, 1b, 2a, 2b, 3, 4 and Dash) have been cloned. 53,61) Investigation of the in vitro functions of these genes has shown that they fall into two groups: one group inhibits CLOCK:BMAL-mediated transcription (repressor type CRYs: zCRY1a, 1b, 2a and 2b), whereas the other group does not inhibit transcription (non-repressor type CRYs: zCRY3, 4 and Dash). 61,62) Despite its structural and functional similarities to the repressor type CRYs, zCry1a transcription is quite different from that of the other repressor type CRYs and is strictly light-dependent (Fig.…”
Section: Redox Signaling Is Involved In the Light Entrainment Of The mentioning
confidence: 99%
“…Reference sequences were selected according to Daiyasu et al (2004) and were also retrieved from the National Center for Biotechnology Information Entrez Protein database (see Figure 1B for corresponding gene identifier numbers). Multiple sequence alignments were carried out using T-COFFEE, ClustalW, and MAFFT with default parameters (Thompson et al, 1994;Notredame et al, 2000;Katoh et al, 2005).…”
Section: Sequence Analysesmentioning
confidence: 99%
“…They absorb light in the blue spectrum and transfer an excited electron from the cofactor FAD to an enzyme-bound cyclobutane pyrimidine dimer (CPD), which is thereby cleaved (Sancar, 1990(Sancar, , 1994Sancar, 1994). Cryptochromes are characterized by an N-terminal photolyase-related (PHR) region without significant photorepair activity and by a C-terminal domain of varying length, which is absent in members of the CRY-DASH subfamily (Daiyasu et al, 2004). The exact function of the CRY-DASH proteins was elusive; however, recent data imply that they are actually photolyases that specifically repair CPDs in single-stranded DNA (Selby and Sancar, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation